METHODS OF MORAL EDUCATION IN THE VIEWS OF ORIENTAL THINKERS AND THE MODEL OF MODERN SPIRITUAL AND MORAL COMPETENCE (Eureka Journal of Humanities and Social Research, 2026)
The article discusses the views of moral education formed in different civilizational spaces of the East and their application in the development of spiritual and moral competencies in the process of modern higher education. The study was conducted on the basis of educational wisdoms and concepts from the heritage of Confucius (China), Mahatma Gandhi (India), Saadi Sherrozi (Iran), Jalal ad-Din Rumi (Anatolia), Nizami Ganjavi (Azerbaijan). The methodology includes conceptual analytical, comparative-historical, case-study and competency modeling approaches. The results reveal the content of methods of moral education (example, interview, discussion, habituation, accounting/reflection, social service) and propose methodological solutions on the example of typical situations in the life of students of Uzbekistan: academic honesty (culture of plagiarism and work with sources), etiquette of digital communication (ethics of group chats), justice of the collective project (contribution and responsibility), cultural management of stress and conflict, professional etiquette (practical discipline). It also proposed a 5-component model of moral competencies: value-goal, cognition-content, behavior-action, reflexion-self-management, social interaction blocks and indicators for their assessment.
Keywords: Ethics education, spiritual and ethical competence, Confucius, Gandhi, Sa'di Sherrozi, Jalal ad-Din Rumi, Nizami Ganjavi, academic honesty, digital ethics, reflexion.